Pelatihan Mindfulness dalam E-Modul sebagai Upaya Mengurangi Math Anxiety Siswa SD dan Memotivasi Pembelajaran berbasis Growth Mindset - Sinaga, Nurul Afni; Ningtyas, Fitri Ayu; Astuti, Widi; Siregar, Togu Nadia; Rahmadani, Rahmadani (Jurnal SOLMA, 2025)
Background: The problems faced by the 31 teachers of Banda Sakti Elementary School's learning community partners include teachers' low understanding in handling students' math anxiety, difficulties in guiding students who are less motivated and limitations in developing digital teaching media such as interactive e-modules. This problem impacts the learning process which is less effective and students' learning motivation is low. The solution offered is training in creating e-modules integrated with mindfulness and growth mindset strategies, then the goal is achieved so that teachers can design teaching materials that can reduce students' learning anxiety and increase their motivation in learning mathematics. Methods: The method is Participatory Rural Appraisal (PRA), with a participatory approach covering five stages: (1) Identification and analysis of the initial situation, (2) Participatory planning, (3) implementation of activities in the form of 3 sessions of  learning, and feedback (5) Evaluation of the program. Participants were given a pretest before the training began and a posttest after the training ended. Results: Based on the evaluation results, the average pretest scores were 48.06%. After the training, the average posttest score increased to 81.29%. These results indicate that the training also effective in improving their pedagogical competence and technological skills. Furthermore, participants were given a satisfaction survey questionnaire after the training. The results indicated that the training was effective and provided tangible benefits to teachers. Conclusion: It needs to be implemented continuously so that teacher competencies continue to develop in line with the challenges of technology-based education.